MANAJEMEN KRISIS KEPARIWISATAAN PADA OBJEK WISATA UMBUL PONGGOK DALAM MENGHADAPI ADAPTASI KEBIASAAN BARU DI ERA PANDEMI COVID- 19 - Larasati Widada Putri; Amni Zarkasyi Rahman; Kismartini - Kismartini (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
Tourism, which is one of the strategic sectors that encourage development and economic growth in a region, must experience problems due to the emergence of the COVID19 pandemic crisis in Indonesia. Umbul Ponggok, which is a source of wealth and tourism potential in Ponggok Village, has also been affected by the COVID-19 pandemic. This condition must be overcome immediately, it is hoped that the COVID-19 pandemic will not be a reason for the cessation of the tourism sector's contribution to the welfare of the people of Ponggok Village. The background of this research is to find out how tourism crisis management is carried out by the Umbul Ponggok management and changes to the 3A elements (Attraction, Accessibility, and Amenities) during the recovery of tourist destinations by adapting to new habits during the COVID-19 pandemic. Through a descriptive qualitative approach using primary and secondary data sources from direct observation, interviews with research informants who were determined based on the Purposive Sampling technique, with key informants determined namely the Director of BUMDes Tirta Mandiri and data from various documents processed directly by Owned Enterprises Desa Tirta Mandiri as well as from books, journals, articles and websites. The results of the study show that tourism crisis management at Umbul Ponggok in facing the COVID-19 pandemic crisis towards recovery with adaptation to new habits does not seem to have mature pre-crisis planning due to unpreparedness and limited management which in turn also triggers some laxity and indiscipline in its implementation.